Investigating the Impact of Business Strategies on the Performance of Startups in Crossing the Valley of Death with a Focus on Kermanshah City - Naderi, Nader; Rezaee , Bijan; Khademi, Arash (Future of Work and Digital Management Journal, 2026)
Startups, as the driving engine of innovation and economic growth, face numerous challenges in their early years, most of which manifest during the critical stage of the “Valley of Death.” This critical period entails problems such as securing financial resources, attracting customers, and maintaining cash flow, which are intensified in environments with infrastructural and economic constraints, such as Kermanshah. This descriptive-survey study was conducted on a statistical population comprising registered startups in Kermanshah. Data were collected using a researcher-developed questionnaire and semi-structured interviews, and data analysis was performed using SPSS version software and statistical tests including correlation and multiple regression. The research findings indicated that all financial, marketing, innovation, and human resources strategies have a positive and significant effect on the performance of startups. Among these, the innovation strategy with a beta coefficient of and the financial strategy with had the greatest impact, while human resources ( ) and marketing ( ) played reinforcing roles. Furthermore, the coefficient of determination of the model ( ) showed that these four strategies jointly explain of the variance in business performance. The results demonstrated that all examined strategies have a positive and significant effect on startup performance. The innovation strategy with a coefficient of and the financial strategy with had the greatest impact on crossing the valley of death, while human resources ( ) and marketing ( ) played complementary roles. Additionally, the coefficient of determination of indicates that these four strategies collectively account for of the variance in business performance. Accordingly, focusing on innovation and financial management should be prioritized, and human resources and marketing strategies should be strengthened as support mechanisms.